Pengaruh Indeks Pembangunan Manusia (IPM) dan Tingkat Pengangguran Terhadap Kemiskinan di Jawa Timur Periode 2020-2022 - Avinda Putri Romadhona; Dewi Ira Agustin; Siti Nahdhiatun Nisa’; Wandha Dhamar Maulana (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
Poverty is a symptom that is experienced by humans because of differences in resources that have an impact on the welfare of human survival thus the level of poverty is related to the level of one’s welfare. People want to have prosperity is a common thing, therefore poverty must be minimized whether it is urban or rural. In East Java, the poverty rate is aiming for an increase in the 2020-2021 period after it decreased in 2022. In the unemployment rate has decreased also accompanied by the Community Development Index (HDI) which has increased, the research uses secondary data taken from the statistics agency for East Java province via the internet to supplement the data. Using multiple linear regression analysis method with the help of softwhare SPSS, the results obtained concluded that poverty in East Java is significantly and negatively affected by the variable HDI.